Evaluating The Performance of Flood Prevention Programs in Bandung Regency: Using Logic Model - Rosy Riani Kusuma; Ida Widianingsih; Sintaningrum Sintaningrum; Rita Myrna (Iapa Proceedings Conference, 2019)
In this era of, the public gives more attention to the achievements of government performance, including the regional government. One of the problems is the repeated floods in the Citarum Watershed. However, because disaster events can occur at any time with different locations, there are difficulties for regional leaders and their staff to measure and evaluate the quality and performance of the disaster management programs that they have carried out, especially in situations of emergency response. The large flood of Upper Citarum has damaged buildings and disrupted infrastructure functions due to 12,654 buildings submerged and damage such as potholes and foundation damage many local roads and the closure of a number of schools and other social buildings. Evaluation of the performance of disaster management programs is needed in order to know program performance to develop and to increase capacity and services performed. This study will expose what has been done by the Bandung District Government to overcome the problem of flooding in the Upper Citarum watershed during the last 3 years and evaluate the performance of the Bandung Regency Government to tackle the problem of floods that have recurred in that area using Logic Model.